Cu-Based Z-Schemes Family Photocatalysts for Solar H2 Production - Rossella Greco; Romain Botella; Javier Fernández-Catalá (Hydrogen, 2023)
Solar photocatalytic H2 production has drawn an increasing amount of attention from the scientific community, industry, and society due to its use of green solar energy and a photocatalyst (semiconductor material) to produce green H2. Cu-based semiconductors are interesting as photocatalysts for H2 production because Cu is earth-abundant, cheap, and the synthesis of its copper-containing semiconductors is straightforward. Moreover, Cu-based semiconductors absorb visible light and present an adequate redox potential to perform water splitting reaction. Nevertheless, pristine Cu-based semiconductors exhibit low photoactivity due to the rapid recombination of photo-induced electron-hole (e−-h+) pairs and are subject to photo corrosion. To remedy these pitfalls, the Cu semiconductor-based Z-scheme family (Z-schemes and S-schemes) presents great interest due to the charge carrier mechanism involved. Due to the interest of Z-scheme photocatalysts in this issue, the basic concepts of the Z-scheme focusing on Cu-based semiconductors are addressed to obtain novel systems with high H2 photo-catalytic activity. Focusing on H2 production using Cu-based Z-schemes photocatalyst, the most representative examples are included in the main text. To conclude, an outlook on the future challenges of this topic is addressed.